Nitrosamines in medicinal products - Katarzyna Dominiak; Marta Lewandowska; Katarzyna Dettlaff (Polish Pharmaceutical Society, 2022)
Nitrosamines are compounds that have a harmful effect on the organisms of animals and humans. The first information about their teratogenic, mutagenic, and genotoxic effects appeared in the mid-twentieth century. The source of nitrosamines in the human environment are, among others, cold cuts, processed meat, drinking water, tobacco smoke, and some plastics. The discovery of the presence of nitrosamines in some medicinal products was received with great concern in 2018. The first group of drugs in which the presence of carcinogenic compounds was proven were sartans (valsartan, losartan, and irbesartan), and then also metformin, ranitidine, nizatidine, rifapentin, and rifampicin. Some of the medicinal products on the market were discontinued, and after the presence of nitrosamines was confirmed, they were withdrawn. Then, the investigations on the cause of the presence of such harmful compounds in the drugs were carried out. It turned out that in the case of three medicinal substances from the group of sartans, nitrosamines were impurities from the synthesis process, formed in the stage of tetrazole ring formation from organic or inorganic azides. In the case of macrolide antibiotics from the ansamycin group, nitrosamines were also process-related impurities, and in the case of metformin, ranitidine and nizatidine, they turned out to be degradation products of medicinal compounds. When it was discovered that nitrosamines could be present in some drugs used in the treatment of hypertension for over 5 years, that is from the last modification of the synthesis by the manufacturer of the drug substance, retrospective observational studies were carried out, in which the level of cancer risk associated with taking contaminated preparations was established. Analytical methods for the determination of nitrosamines in medicinal substances and medicinal products based on liquid or gas chromatography coupled with mass spectrometry have been developed. Moreover, testing procedures and stringent guidelines for the content of nitrosamines were introduced to the 10th edition of the European Pharmacopoeia to guarantee the appropriate quality of drugs, ensuring safe therapy.